Giant sea creatures - Kunhardt, Edith; Reid, Fiona (New York : Golden Book ; Racine, Wis. : Western Pub. Co., 1984)
Describes the physical and behavioral characteristics of many of the largest animals living in the shallow and deep areas of the ocean.
Includes index.
Bibliography: p. 44.
K-3
Keywords: Marine fauna -- Miscellanea -- Juvenile literature; Marine animals; Marine animals; Marine animals